2001
DOI: 10.3727/000000001783992696
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Approaches to Control Gene Expression

Abstract: A current goal in molecular medicine is the development of new strategies to interfere with gene expression in living cells in the hope that novel therapies for human disease will result from these efforts. This review focuses on small-molecule or chemical approaches to manipulate gene expression by modulating either transcription of messenger RNA-coding genes or protein translation. The molecules under study include natural products, designed ligands, and compounds identified through functional screens of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 79 publications
0
49
0
Order By: Relevance
“…[55][56][57]. In this study we employed a human COL1A1 promoter to examine whether two DNA-binding drugs, mitoxantrone and WP631, interfered with the formation of Sp1-DNA complexes and inhibited COL1A1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57]. In this study we employed a human COL1A1 promoter to examine whether two DNA-binding drugs, mitoxantrone and WP631, interfered with the formation of Sp1-DNA complexes and inhibited COL1A1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the molecules screened by Hebert and colleagues, a number of other natural and synthetic ligands have been identified that possess the ability to bind duplex DNA (Gottesfeld et al, 2000;Wemmer and Dervan, 1997). Among these molecules, the pyrrole-imidazole polyamides are unique in that they can be programmed to bind predetermined DNA sequences (Dervan and Edelson, 2003).…”
Section: Dna Ligands To Increase Fxn Gene Expressionmentioning
confidence: 99%
“…Polyamides are synthetic DNA binding molecules designed to recognize and bind to specific sequences in the minor groove of the double helix with affinities comparable with those of DNA-binding proteins (1,2). Polyamides comprised of pyrrole (Py) 1 and imidazole (Im) amino acids are connected through a ␄-aminobutyric acid (␄) linker to create a hairpin structure.…”
mentioning
confidence: 99%